Persepsi Mahasiswa Tentang Pembelajaran yang Ideal Membentuk Lulusan Berdaya Saing di Era Millenial: Studi Terhadap Mahasiswa Prodi PAI UIN Sumatera Utara Medan - Rahmat Rifai Lubis; Mindi Mentari; Fitrianingrum Br Pane; Mustika Risti; May Saroh (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2022)
Ideal learning in the millennial era is especially important for students of the PAI study program, where the mold of the PAI study program will later become a figure that builds the morals and character of students in the millennial era. In order to prepare the Millennial generation which is expected by the nation, religion and state in facing challenges in the era of globalization, it is necessary to have serious attention from the government in the field of education that is more targeted and measurable so that the results can be felt and utilized for the benefit of the nation and the State. Students' perceptions of learning in the PAI UIN-SU study program are appropriate for students of the Islamic religious education study program. Because the learning that is applied is suitable for Islamic religious education majors, namely, to form ideal PAI teacher candidates. As with learning educational planning then studying various learning strategies, teaching the teaching profession and so on. Which basically refers to the aim of the PAI study program, which is to form ideal PAI teacher candidates.